Hierarchical Fabrication of Plasmonic Superlattice Membrane by Aspect-Ratio Controllable Nanobricks for Label-Free Protein Detection - Chen, Yi; Liu, Huang; Yin, Haojing; Zhu, Qi; Yao, Gang; Gu, Ning (Frontiers in Chemistry, 2020)
Plasmonic superlattice membrane exhibits remarkable functional properties that are emerging from engineered assemblies of well-defined “meta-atoms”, which featured as a conceptually new category of two-dimensional optical metamaterials. The ability to build plasmonic membrane over macroscopic surfaces but nanoscale ordering is crucial for systematically control the light-matter interactions, and represents considerable advance for bottom-up fabrication of soft optoelectronic devices and circuits. By rational design the novel nanocrystals and engineering the packing orders, the hybridized plasmon signature can be customized, which promotes controllable near-field confinement for surface-enhanced Raman scattering (SERS) based detection. However, building such 2D architectures has proven to be remarkably challenging due to the complicated interparticle forces and multiscale interactions during self-assembly. Here, we report on the fabrication of ultralong-nanobrick-based giant plasmonic superlattice membranes as high-performance SERS substrates for ultrasensitive and label-free protein detection. Using aspect-ratio controllable short-to-ultralong nanobricks as building blocks, we construct three distinctive plasmonic membranes by polymer-ligand-based strategy in drying-mediated self-assembly at the air/water interfaces. The plasmonic membranes exhibit monolayered morphology with nanoscale assembled ordering but macroscopic lateral dimensions, inducing enhanced near-field confinement and uniform hot-spot distribution. By choosing 4-aminothiophenol and bovine serum albumin (BSA) as a model analyte, we establish an ultrasensitive assay for label-free SERS detection. The detection limit of BSA can reach to 15nM, and the enhancement factor reached 4.3×10E5, enabling promising avenue for its clinical application in ultrasensitive biodiagnostics.